Hot deformation behavior and microstructural evolution of as-cast 304L antibacterial austenitic stainless steel. (16th February 2018) - Li, Juan; Zhao, Guanghui; Chen, Huiqin; Huang, Qingxue; Ma, Lifeng; Zhang, Wei
Abstract: Hot deformation behavior of as-cast antibacterial austenitic stainless steel with 2.42% copper was investigated in the temperature range of 900 °C–1150 °C, and the strain rates ranged from 0.01 to 20 s −1 . At strain rates higher than 1 s −1, the flow stress curves were corrected by considering adiabatic heating. Kinetic analysis indicated that the hot deformation activation energy of the steel was 375.65 kJ mol −1 . The dynamic recrystallization (DRX), misorientation, and twins were analyzed using optical microscope or electron backscatter diffraction. The results showed that DRX mechanism in hot deformation mainly corresponded to discontinuous recrystallization at high temperature and with a high rate. By increasing the temperature and strain rate, the recrystallization degree and the twin ratio increased simultaneously. Both of these factors promoted one another.